Political recognition and cultural identity of minorities: what is their meaning in the case of Khoisan in South Africa? - Kukauka, Nadzeya (Department of Religious Studies, 2024)
Post-apartheid South Africa committed to the political and cultural recognition of ethnic minorities. The commitment was instilled in the Bill of Rights of 1996, the United Nations Declaration on the Rights of Indigenous Peoples adopted by South Africa in 2016, and in the direction toward repair of past injustices that transpired in the Truth and Reconciliation Commission report of 1994. However, attempts to politically recognise Khoisan are producing some significant challenges. This work argues that without a deeper understanding of political and philosophical recognition, social justice may be inadequately distributed and may lead to misrepresentation and the extension of injustices. I will argue that the absence of recognition, or misrecognition, inflicts harm and becomes a form of oppression that preserves a distorted and reduced mode of being for Khoisan, created in the colonial past. In chapter 1, I will illustrate how harmful identity politics of colonial and apartheid times produced identities of “primitive” people, unworthy of political membership. In chapter 2, I will trace the development of the philosophical concept of recognition in Europe and its path in Africa using the theoretical framework of Axel Honneth, Charles Taylor, Mahmood Mamdani and Milton Bennett. It will be shown that the blindness of indirect rule and the insufficient intercultural competence perpetuate the misrecognition of Khoisan. In chapter 3, I will analyse post-apartheid legislations aimed towards the upliftment of traditional communities. The legal misrecognition will transpire from the analysis of the Traditional and Khoisan Leadership Act of 2019. The last chapter will illustrate how TKLA2019 may misrepresent Khoisan ethics and the historical vitality of traditional governance. In conclusion, I will evaluate how the current socio-political dynamics affects just governance and decolonial understanding of sovereignty.